Struktur Komunitas Mangrove di Kecamatan Bukit Batu Kabupaten Bengkalis Provinsi Riau - Fania Suffy Mulyani; Mubarak Mubarak; Bintal Amin (Universitas Riau, 2024)
This research was conducted in Februari-Mei 2022. This research aims to know the types of mangrove and analyzing the structure of the mangrove community. The method used in this research is ground checks which was carried out at 6 (six) station in Bukit Batu Sub-distrcit with line transect method and data processing covered all areas in the Bukit Batu Sub-district. Based on the results this research found 10 types of mangroves; R. apiculata, R. mucronata, A. alba, A. marina, S.caseolaris, B. gymnorrhiza, B. sexangula, X. granatum, C. tagal, and N. fruticans. The density of mangrove in Bukit Batu Sub-district is into the medium criteria in the tree category was 1041 ind/ha and in the sapling category was 1163 in/ha. The condition of mangrove vegetation in Bukit Batu Sub-district are dominated by R. apiculata in the tree category with an Important Value Index was 106,13% and sapling category with an Important Value Index was 108,77%.